Australian residential aged care home staff experiences of implementing an intervention to improve palliative and end‐of‐life care for residents: A qualitative study. (6th September 2022) - Vilapakkam Nagarajan, Srivalli; Poulos, Christopher J.; Clayton, Josephine M.; Atee, Mustafa; Morris, Thomas; Lovell, Melanie R.
Abstract: Access to high‐quality and safe evidence‐based palliative care (PC) is important to ensure good end‐of‐life care for older people in residential aged care homes (RACHs). However, many barriers to providing PC in RACHs are frequently cited. The Quality End‐of‐Life Care (QEoLC) Project was a multicomponent intervention that included training, evidence‐based tools and tele‐mentoring, aiming to equip healthcare professionals and careworkers in RACHs with knowledge, skills and confidence in providing PC to residents. This study aims to understand: (1) the experiences of healthcare professionals, careworkers, care managers, planners/implementers who participated in the implementation of the QEoLC Project; and (2) the barriers and facilitators to the implementation. Staff from two RACHs in New South Wales, Australia were recruited between September to November 2021. Semi‐structured interviews and thematic data analysis were used. Fifteen participants (seven health professionals [includes one nurse, two clinical educators, three workplace trainers, one clinical manager/nurse], three careworkers and five managers) were interviewed. Most RACH participants agreed that the QEoLC Project increased their awareness of PC and provided them with the skills/confidence to openly discuss death and dying. Participants perceived that the components of the QEoLC Project had the following benefits for residents: more appropriate use of medications, initiation of timely pain management and discussions with families regarding end‐of‐life care preferences. Key facilitators for implementation were the role of champions, the role of the steering committee, regular clinical meetings to discuss at‐risk residents and mentoring. Implementation barriers included: high staff turnover, COVID‐19 pandemic, time constraints, perceived absence of executive sponsorship, lack of practical support and systems‐related barriers. The findings underline the need for strong leadership, supportive organisational culture and commitment to the implementation of processes for improving the quality of end‐of‐life care. Furthermore, the results highlight the need for codesigning the intervention with RACHs, provision of dedicated staff/resources to support implementation, and integration of project tools with existing systems for achieving effective implementation outcomes.